2020
DOI: 10.3389/fpls.2020.00405
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study and Genomic Prediction Elucidate the Distinct Genetic Architecture of Aluminum and Proton Tolerance in Arabidopsis thaliana

Abstract: Under acid soil conditions, Al stress and proton stress can occur, reducing root growth and function. However, these stressors are distinct, and tolerance to each is governed by multiple physiological processes. To better understand the genes that underlie these coincidental but experimentally separable stresses, a genome-wide association study (GWAS) and genomic prediction (GP) models were created for approximately 200 diverse Arabidopsis thaliana accessions. GWAS and genomic prediction identified 140/160 SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 85 publications
2
21
0
Order By: Relevance
“…In Arabidopsis, it has been reported that the ELP of AtALMT1 is associated with Al tolerance level among natural accessions (Hoekenga et al, 2006, Nakano et al, 2020. Besides, the Al-inducible AtMATE expression secondly contributes to Al tolerance in a manner similar to AtALMT1 (Liu et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In Arabidopsis, it has been reported that the ELP of AtALMT1 is associated with Al tolerance level among natural accessions (Hoekenga et al, 2006, Nakano et al, 2020. Besides, the Al-inducible AtMATE expression secondly contributes to Al tolerance in a manner similar to AtALMT1 (Liu et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…The information of the position and description of the Arabidopsis genes located around the GWAS-detected SNPs was obtained from the Araport11 database (http://www.arapo rt.org/; Cheng et al, 2017). The information of the Al tolerance levels of the accessions belonging to the CA population was obtained from Nakano et al, (2020).…”
Section: Phylogenetic Analysis and Gwasmentioning
confidence: 99%
See 2 more Smart Citations
“…To estimate how effective the SNPs were in explaining the variation and to validate the potential of the GWAS-associated SNPs in the GP model, a GP analysis by GBLUP (RR) was performed using the SNPs with the lowest p -values (top-ranked) in the GWAS, as described by Nakano et al (2020) with slight modifications 65 . The cumulative effects of the linked loci were estimated using 20–300 top-ranked SNPs (at 20 SNPs intervals).…”
Section: Methodsmentioning
confidence: 99%